Bentuk Perkembangan dan Penafsiran Judi dalam Pandangan Al-Baqarah 219 dan Al-Maidah 90-91 - Salim, Fadli; Andito, Muhammad Sasri; Hanif, Muhammad; Aziz Efendi, Ahmad Abdul (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
The development of technology is becoming increasingly sophisticated, which has influenced life and brought convenience to social life, including gambling practices in society. In the past it was done by gathering in one place to do it, now it can be done anywhere and anytime by using a mobile phone. Although the Qur'an explicitly forbids gambling, it cannot be denied that gambling also brings benefits to its perpetrators. This has been explained in the Qur'an that gambling has benefits but also has more mudhorat. Therefore, this study aims to discuss the development of gambling from time to time and its classification as well as how the interpretation of the scholars of tafsir in answering verses that are difficult to understand textually by the community on the verse of the Qur'an that discusses gambling. The research uses a qualitative method with a literature study approach by collecting various studies on gambling to find out which are included in gambling as well as the true meaning of Surah Al-Baqarah verse 219 and Al-Maidah verse 19 in answering problems in society.